ANALISIS WACANA KRITIS DALAM PERSPEKTIF NORMAN FAIRCLOUGH - Munfarida, Elya (Fakultas Dakwah IAIN Purwokerto, 2014)
Discourse analysis has been a study that attracts many intelectuals of various disciplines to discuss about, generating the emergence of theories of their own perspectives. Many criticisms for the theories also show that intelectuals are more interested in this field leading to make discourse analysis as a multidisciplinary study. Based on this ground, Norman Fairclough seeks to reconstruct discourse theory as a criticism to the existing theories, which tends to be side-emphasis and partial on the basis of their own discipline. Combining three traditions, i.e. linguistic, interpretative, and sociological traditions, he offers a discourse model integrating three dimensions: text, discourse practice, and social practice. Each dimension has its area, process, and analysis model, in which all of them dialectically connect to one another. In addition, Fairclough also formulates another important concept, namely intertextuality, which affirms the interrelation of various texts and discourses to a text. This concept will also create ideological effect of structuration and restructuration of the prevalent discourse order. When power and ideology embed in a discourse, intertextuality will function as a mechanism for maintaining and changing the domination relation.